THE INFLUENCE OF SYSTEMATIC DECENTIZATION TECHNIQUES GROUP GUIDANCE SERVICES ON STUDENTS AT SMA NEGERI 2 LAWE BULAN - Selviana; Nurasyah (Media Inovasi Pendidikan dan Publikasi, 2024)
Speaking anxiety is a form of real feeling of fear or anxiety when speaking in public. Anxiety can occur due to feelings of pressure experienced by a person because anxiety is an unpleasant feeling and causes fear, tension and worry which can lead to certain behavior. Students who have anxiety about speaking can be seen from the characteristics of an increasingly rapid heartbeat, a trembling voice, trembling legs, difficulty remembering material when speaking, and feeling embarrassed when speaking. To overcome this problem, a teacher does not only give directions or lectures. However, a teacher needs to set an example that allows students to learn about things that cannot be learned only through the lecture process. One example that can be applied to this problem is by using systematic desensitization techniques. Systematic desensitization is a technique to help students reduce their anxiety. This type of research is quantitative pre-experimental. This research also uses a one group pretest and posttest design. In this research, the focus is on the effect of systematic desensitization techniques, group guidance services, systematic desensitization techniques on students' speaking anxiety at SMA Negeri 2 Lawe Bulan using data collection techniques using questionnaires and data analysis. Thus, it can be stated that group guidance using systematic desensitization techniques can have an effect on reducing students' speaking anxiety at SMA Negeri 2 Lawe Bulan.